Interdepartmental dermatology: Characteristics and impact of dermatology inpatient referrals at a teaching hospital in Eastern India - Satyendra Nath Chowdhury; Indrasish Podder; Abanti Saha; Debabrata Bandyopadhyay (Wolters Kluwer Medknow Publications, 2017)
Background: Dermatology is primarily considered to be an outpatient-centered specialty. However, several inpatient admissions to other specialties require dermatologic consultation for optimum management. Aims: To analyze the causes of inpatient dermatology referrals, departments sending referrals, and impact of dermatology consultation on patient management. Materials and Methods: We conducted a cross-sectional study by analyzing the records of 486 patient referrals over a 4-year period. The demographic details, specialties requesting consultation, cause of referral, and dermatological advice have been recorded and analyzed. Results: Dermatology consultation changed the dermatologic diagnosis and treatment of almost two-thirds of patients. General medicine requested the maximum number of referrals, "skin rash" being the most common cause for referral. Accurate diagnosis on referrals was provided by only 30.2% of nondermatologists. Common dermatological disorders were often misdiagnosed by these physicians, and dermatology referrals had significant impact on the diagnosis and subsequent management of these patients. Conclusion: While dermatologic referral leads to improved patient care, there is a need for better training of nondermatologists enabling them to recognize and treat common dermatoses.